The recursivity of internet governance research - José van Dijck; Bernhard Rieder (Internet Policy Review, 2019)
This special of Internet Policy Review is the second to bring together the best policy-oriented papers presented at the annual conference of the Association of Internet Researchers (AoIR). The conference in Montréal, in October 2018, was organised around the theme of "Transnational materialities". As explained in the editorial to this issue, the contributions map the larger debate on internet governance research in terms of perspectives rather than disciplines. The eleven papers in this span a wide range of topics, including normative perspectives on how platforms shape democracy, conceptual perspectives on how to think platform power, and social and legal views on data-driven governance.
Keywords: 300; Association of Internet Researchers; Platform governance; Data governance; Algorithmic governance